2021
DOI: 10.3892/etm.2021.10528
|View full text |Cite
|
Sign up to set email alerts
|

KIF2C promotes the proliferation of hepatocellular carcinoma cells in vitro and in vivo

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies with high mortality and morbidity rates. In recent years, HCC targeted therapy has gained increasing attention. Due to the heterogeneity and high metastasis of HCC, more effective therapeutic targets are needed. Kinesin family member 2C (KIF2C), also known as mitotic centromere-associated kinesin, is a microtubule-based motor protein which is involved in a variety of important cellular processes, such as mitosis. The effects of KIF2C on canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…Previous research has revealed that KIF2C is substantially expressed in liver cancer (17,19,26,27), breast cancer (28), endometrial carcinoma (20), lung cancer (29,30), glioma (31), bladder cancer (32), colorectal cancer (33), esophageal squamous cell carcinoma (34), cervical cancer (18), and thyroid cancer (35). The results of our pan-cancer analysis indicated that KIF2C was highly expressed in 28 tumors, including PCa, which was consistent with previous results reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has revealed that KIF2C is substantially expressed in liver cancer (17,19,26,27), breast cancer (28), endometrial carcinoma (20), lung cancer (29,30), glioma (31), bladder cancer (32), colorectal cancer (33), esophageal squamous cell carcinoma (34), cervical cancer (18), and thyroid cancer (35). The results of our pan-cancer analysis indicated that KIF2C was highly expressed in 28 tumors, including PCa, which was consistent with previous results reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Cell viability assay and cell cycle distribution analysis demonstrated no significant alterations between the cell lines (Figure S1A,B). These findings are in contrast to two recent publications in thyroid carcinoma and hepatocarcinoma cells, which showed that a knockdown of MCAK leads to a reduced proliferation rate in these cell types [33,34]. This contradiction might be explained because both publications used a transient siRNA transfection system for their experiments or due to a cell type specific effect.…”
Section: Characterization Of Hela/rpe Crispr/dcas9 Sgmcak Knockdown (Crispri) and Overexpression (Crispra) Cell Linescontrasting
confidence: 94%
“…The proteins sorted according to the combined score were as follows: CCNB2, CDK1, PLK1, CCNB1, CDC20, KIF2C, RPS27A, AURKB, UBB, and UBA52. Previous research has verified that CCNB2, CCNB1, CDK1, PLK1, CDC20, KIF2C, RPS27A, and AURKB play vital roles in regulating the cell cycle transition, radiosensitivity and cell proliferation in various tumors ( Wang et al, 2014 ; Nie et al, 2020 ; Zou et al, 2020 ; Gao et al, 2021 ; Gheghiani et al, 2021 ; Zhao et al, 2021 ). From the PPI network of GTSE1, we speculate that GTSE1 plays an important role in the cell cycle transition and malignant proliferation of tumors.…”
Section: Resultsmentioning
confidence: 96%